A model for vehicle tracking and monitoring systems adoption in the Kenya Police Service - Ngumbi, Damaris Ndunge (Strathmore University, 2016)
The presence of police patrol cars in Kenya has not increased as it was expected in the wake of the leasing of hundreds of emergency response vehicles to the police in 2014. Rogue police officers use police cars for personal errands. The police vehicles are sometimes fuelled at stations authorized by the Kenya police service on the pretext that they are on official duty. Efficient use of police resources and transparency has been a top agenda of police reforms in Kenya. It is for this reason that this research sought to establish the extent of vehicle tracking and monitoring systems adoption in the Kenyan policy service. This research used explanatory research design. The population of this research consisted of all the 110 police stations and police posts in Nairobi County. A sample of 57 police stations and police posts was selected. The research used primary data that was collected by use of questionnaires. The research used both descriptive statistics and inferential statistics in the analysis. The study further conducted structural modeling analysis using the partial least square to validate the proposed model. SPSS-Amos was used for data analysis. The results of this study showed that technology awareness, environmental factors, financial resources and technological complexity significantly affected both perceived usefulness and perceived ease of use of vehicle tracking and monitoring systems. The findings further showed that perceived usefulness had a positive and significant relationship with intention to use the vehicle tracking and monitoring systems. The proposed model comprised of four dimensions technology awareness, environmental context, financial resources and Technological complexity. Validity tests proved that the variables in the model were significant in explaining the behavioral perceived usefulness and perceived ease of use of police towards vehicle tracking and monitoring systems use. Perceived Usefulness and Perceived Ease of Use were also significant in explaining the behavioral intention to use of police towards vehicle tracking and monitoring systems use. The final model accounted for a significant variance of behavioral intention towards vehicle tracking and monitoring systems use. The study also recommends that the Kenya police service should train their officers on the vehicle tracking and monitoring systems and also allocate funds in their budget to implement the installation and training on tracking and monitoring systems.
Submitted in partial fulfillment of the requirements for the Degree of Master of Science in Computer Based Information Systems
Keywords: Vehicle tracking; Monitoring system; Kenya Police Service